A scientometric study and a bibliometric review of the literature on the design and construction of semi-flexible pavement - Ali, Rania; Al-Humeidawi, Basim (Al-Qadisiyah journal for engineering science, 2023)
In last years, a new type of pavement has gained popularity, this type is called Semi-Flexible Pavement (SFP). It consists of porous asphalt with high air voids between (25-35) % filled with cementitious grout materials. This type of pavement substance offers substantial advantages over both common types of pavements (concrete and flexible) such as good resistance to rutting and durability. SFP is considered an alternative pavement to exceed the drawbacks that occur for both flexible and concrete pavements. SFP has good features against permanent deformation, oil spillage, and fatigue resistance. Previous studies have shown that it can be used in a variety of applications such as highways, motorways, bridge deck pavement, tunnels, industrial areas with industrial equipment traffic, airport aprons, and stations. The goal of this research is to identify and compile the most significant research papers using the Web of Science (WOS), analyze the data using the VOS viewer software, as well as learn which countries and institutions had published the most articles relating to the subject of cementitious grout material as it relates to semi-flexible. It was also done to learn more about the authors and their collaboration. In addition to knowing the keywords that will aid researchers in their research on this topic, using these studies to better understand the elements that affect how well semi-flexible mixtures and grouts perform such as porous asphalt Mixture gradation and grout material components.